2019
DOI: 10.1007/s11240-019-01607-5
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Ribes nigrum (L.) dormant buds: recovery via in vitro culture to the field

Abstract: Cryopreservation of dormant buds can be a feasible method for long term preservation of clonally propagated woody plants.In the present study, dormant buds of blackcurrant (Ribes nigrum L) cultivar Mortti were cryopreserved. Twig segments from greenhouse and field grown plants were cooled at their natural moisture content at the rate of 0.17 °C min −1 from zero to −38 °C, immersed in liquid nitrogen and stored in liquid nitrogen vapor. The post-cryopreservation regrowth of buds was evaluated in vitro and viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
9
0
3
Order By: Relevance
“…However, it is important to assess the resilience of cryostored plants when grown under eld conditions as this is ultimately the system used for production. Rantala et al (2019) investigated the recovery of cryopreserved shoot tips of blackcurrant and recorded the yield of berries harvested in two consecutive seasons. As reported in the present study, those authors found no differences in the yield of cryostored and non-stored plants.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to assess the resilience of cryostored plants when grown under eld conditions as this is ultimately the system used for production. Rantala et al (2019) investigated the recovery of cryopreserved shoot tips of blackcurrant and recorded the yield of berries harvested in two consecutive seasons. As reported in the present study, those authors found no differences in the yield of cryostored and non-stored plants.…”
Section: Resultsmentioning
confidence: 99%
“…yang sesuai seperti adanya auksin dan senyawa penting lainnya untuk berakar di plantlet Lavandula angustifolia L. Penyimpanan dalam nitrogen cair selama 45 menit atau 1 jam sudah dapat menjadi indikator kemampuan sampel mata tunas disimpan dalam jangka panjang (dorman). Penyimpanan dalam uap nitrogen dengan kisaran suhu sekitar -140˚C juga dilakukan pada tunas dorman dari kebun buah Ribes nigrum L [15]. Hasil ini memberikan harapan bahwa stek super mini dapat disimpan dalam jangka panjang.…”
Section: A B Cunclassified
“…Hal ini dikarenakan kandungan air yang banyak akan menjadi kristal es bila direndam di nitrogen cair. Pada tanaman buah berkayu lainnya, perlakuan slow cooling (pendinginan bertahap) sebelum dicelup di nitrogen cair lalu disimpan hanya dalam uap nitrogen cair juga merupakan yang terbaik seperti pada mata tunas dorman Ribes nigrum L. dengan daya hidup mencapai 83% [15].…”
Section: A B Cunclassified
“…Cryopreservation of blackcurrant has been studied for a long time using a variety of cryopreservation methods and protocols (Benson et al 1996;Reed et al 2001Reed et al , 2004Reed et al , 2005Johnston et al 2007;Harding et al 2009;Green and Grout 2010;Rantala et al 2019). Different cryopreservation techniques are employed for Ribes species in USDA-ARS National Plant Germplasm System, Plant and Animal Genetic Resources Preservation Unit, Fort Collins, CO (Jenderek and Reed 2017).…”
Section: Introductionmentioning
confidence: 99%